Pemanfaatan Jantung Pisang Sebagai Solusi Pangan Lokal Untuk Kemandirian Desa Tinelo Kecamatan Tilango Kabupaten Gorontalo - Abdjul, Tirtawaty; Nurhayati, Nurhayati (Universitas Negeri Gorontalo, 2025)
This community service activity aims to increase the utilization of banana hearts as a local food solution with economic value for the people of Tinelo Village, Tilango District, Gorontalo Regency. The method used is Participatory Action Research (PAR) thru five main stages: preparation, product design, training, mentoring, and evaluation. The results of the activity show that training on processing banana heart into garo rica meat was able to increase participants' knowledge, skills, and creativity in processing local food ingredients. The organoleptic test showed an average score of 4.5 (very satisfactory category), with the taste aspect receiving the highest score (4.9). Meanwhile, the results of the participant satisfaction survey showed an average score of 4.4 (satisfactory category), indicating that the training materials, facilities, and benefits were considered relevant and useful. This finding confirms that banana heart has the potential to be processed into innovative, healthy, and high-value products, while also supporting food diversification and food security based on local wisdom. Thus, this activity not only produces alternative food products but also makes a real contribution to community empowerment and strengthening the village economy